Gambaran Pengetahuan Pedagang dan Kandungan Formalin pada Buah Impor yang di Jual di Pasar X Kota Palembang - Jerni Puspita Shatara; Diah Navianti; Kamsul Kamsul; Ayu Febri Wulanda; Miftahurrizqiyah Miftahurrizqiyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Formalin is a hazardous chemical that is banned from use in food, but is still found in imported fruit. Traders have an important role in preventing the circulation of food with formaldehyde, so the knowledge of traders about the dangers of formaldehyde needs to be studied. Objective: This study aims to determine the knowledge of traders and formalin content in imported fruit sold in X Market, Palembang City in 2025. Methods: This study used a quantitative approach with a descriptive design. The population in this study were all imported fruit traders in X Market totaling 9 people who served as respondents. The fruit samples tested were 24 samples consisting of apples, pears, and grapes. Data were collected through questionnaires and laboratory tests using formalin test kit. Results: The results showed that all traders (100%) had a good level of knowledge about formalin. Of the 24 fruit samples tested, 21 samples (87.5%) did not contain formalin and 3 samples (12.5%) showed positive results, all of which were from grapes. Conclusion: The majority of traders had good knowledge about formaldehyde, but formaldehyde was still found in some imported fruits, especially grapes.